1999
DOI: 10.1002/(sici)1098-2752(1999)19:3<128::aid-micr2>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

An absorbable pinned-ring device for microvascular anastomosis of vein grafts: Experimental studies

Abstract: In the rabbit, posterior facial vein segments were grafted to the femoral arteries using either conventional suture technique or a mechanical absorbable pinned-ring device. The purpose of this study was to compare patency rates and anastomotic times for the two different methods. The anastomoses were evaluated macroscopically and using light and scanning electron microscopy. The grafts anastomosed with the absorbable rings exhibited 100% patency, while only 83% of the sutured grafts were patent. The mean anast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, an 11% failure rate caused by separation of the absorbable coupler after anastomosis has been reported. Another study reported that couplers containing hook-shaped pins increased the frictional force of the pins attaching to the ring to prevent separation of the couplers 15 . Although the study reported complete patency of this coupler, it was composed of an absorbable ring and non-absorbable stainless pins; therefore, it was not completely absorbable.…”
Section: Discussionmentioning
confidence: 99%
“…However, an 11% failure rate caused by separation of the absorbable coupler after anastomosis has been reported. Another study reported that couplers containing hook-shaped pins increased the frictional force of the pins attaching to the ring to prevent separation of the couplers 15 . Although the study reported complete patency of this coupler, it was composed of an absorbable ring and non-absorbable stainless pins; therefore, it was not completely absorbable.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical pressure due to a rigid, non-compliant device may also contribute to medial atrophy [18]. The regenerated tissue has less elasticity than a normal vessel, suggesting that mural atrophy may be induced by periodically applied vascular pressure [17,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing these issues, a variety of alternative techniques attempting to eliminate the intraluminal suture have been attempted with limited success. In the past 50 years sutureless techniques utilizing rings/couplers, [9][10][11][12][13][14][15] clips, 8,[16][17][18] stents, [19][20][21][22] and adhesives [23][24][25][26][27] have been described. While achieving patency rates similar to suture anastomosis, these techniques have been associated with increased inflammation due to foreign body response, friction with erosion into adjacent tissue, tissue toxicity resulting in vessel wall necrosis, and aneurysm formation.…”
Section: Introductionmentioning
confidence: 99%